Development and biochemical characteristics of a monoclonal antibody against prM protein of Tembusu virus - Siming Zhu; Yi Tang; Youxiang Diao (Poultry Science, 2023)
ABSTRACT: Tembusu virus (TMUV), a pathogenic member of the Flavivirus family, is an infectious diseases that seriously jeopardize duck health in 2010 in China. TMUV disease causes significant economic losses to the duck industry. This study aimed to prepare monoclonal antibodies against TMUV prM protein and to identify their epitopes. The 501bp prM gene was amplified to the pET-32a prokaryotic expression vector and expressed as a recombinant protein of size 38 KD in Escherichia coli. The purified recombinant proteins were inoculated into BALB/c mice to generate splenic lymphocytes capable of secreting anti-prM antibodies, and hybridoma cells were obtained after fusion with SP2/0 cells. A new hybridoma cell line named B27, which stably secreted IgG1-antibody against TMUV prM with high antibody titers up to 1:1:3,276,800 was screened. This monoclonal antibody (mAb) is well specific and can be used for ELISA/Western-blot (WB)/indirect fluorescence assay (IFA) etc. The mAb B27 has poor neutralization ability and concentration dependence, with a maximum neutralization degree of 23.87% at antibody dilution 10−6. Next, we truncated prM gene and expressed the truncated protein to screen antigen epitopes. The mAb's linear antigen epitope of the TMUV prM protein was first identified and was accurate to 6 consecutive amino acids 59GYEPED64, which located in the pr protein. Bioinformatic analysis showed that this antigenic epitope was located on the surface of the antigen, which was conducive to the direct contact of antigen antibody and conformed to the properties of antigenic epitopes. In addition, its 6 amino acids are highly homologous among 27 published TMUV strains, indicating that its epitope is stable. This study will help to further understand the protein structure and the function of prM, and lay the foundation for establishing specific prM detection methods and the mechanistic study of TMUV prM protein.